Anonymous Communication within Highly Repressive Regions - Kamali, Sina (University of Waterloo, 2025)
Repressive governments are increasingly resorting to restricting the flow of information during times of political unrest or civil resistance. In recent years, this restriction has taken new forms, expanding beyond traditional censorship tactics such as IP and DNS blocking to the use of Intranets (internal networks) and complete internet blackouts. To address this, many tools have been proposed to support users during such bleak times. However, most of these tools either overlook the importance of user anonymity or underestimate the lengths to which a censor might go to de-anonymize users. In this thesis, we propose two new tools to help users reclaim their freedom and privacy under these restrictive conditions. First, we present Anix, an anonymous, blackout-resistant microblogging app that supports message endorsing, allowing users to avoid falling victim to misinformation, even without internet access. Second, we introduce Huma, a censorship circumvention tool that operates via web protocol tunneling and leverages deferred traffic replacement to counter a wide range of adversarial attacks. Additionally, Huma can function as a blocking-resistant anonymous communication system within Intranets. Together, these tools offer secure and private solutions for users facing the aforementioned restrictive scenarios. We implement and evaluate both tools to demonstrate their practicality and release our code as an open-source contribution to the community.
Keywords: SOCIAL SCIENCES::Statistics, computer and systems science::Informatics, computer and systems science